The device, the self and the other: A review of the self-tracking culture - Denis Iorga (Journal of Comparative Research in Anthropology and Sociology, 2019)
This paper takes self-tracking culture as the subject matter and provides an example of systematic academic literature review that explores the relationship between culture and nature. It illustrates how the embedding trajectory of a technological artefact in the social sphere can be revealed by a categorization process that uses concepts from different knowledge fields (anthropology, psychology, system studies etc.). Moreover, it shows how the interactions between core values of late modernity and core values of modernity and pre-modernity allow the emergence of a conflicting social mechanism of the self-tracking culture. From object to practices, the cultural embedding process of self-tracking devices is described as a function of their hardware or software nature, their self or body focus, their private or collective degree of exposure and their pushed or imposed degree of autonomy. The underling cultural mechanism of the self-tracking culture is portrayed in terms of a balancing loop between the purchasing behaviour motivated by late modernity values, practices created around the device, subjectivity/objectivity values-conflict and agency/trust beliefs variations.